2021
DOI: 10.1002/cam4.3710
|View full text |Cite
|
Sign up to set email alerts
|

Immune signature as predictive marker for response to checkpoint inhibitor immunotherapy and overall survival in melanoma

Abstract: In 2018, the global incidence of melanoma was 287,723 cases and is predicted to rise. Worldwide, malignant melanoma represents 2.6% of newly diagnosed cancer cases (ASR, age-standardized incidence rate) and is one of the most fatal types of skin cancers. 1 One of the current strategies to treat late-stage melanoma is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Analysis of peripheral blood mononuclear cells (PBMCs) via flow cytometry, before and during treatment with ipilimumab, indicated that patients with low frequencies of circulating Lin − CD14 + HLA-DR - M-MDSCs showed an improved clinical response to this therapy [ 103 ]. These data confirm similar findings in other studies in metastatic melanoma patients treated with ipilimumab [ 104 , 105 , 106 ]. Current research is focused on identifying a reliable and clinically relevant method to use MDSC frequency as a biomarker for the clinical response to ipilimumab in melanoma patients [ 107 ].…”
Section: Role Of Mdscs In Resistance To Immunotherapeuticssupporting
confidence: 93%
“…Analysis of peripheral blood mononuclear cells (PBMCs) via flow cytometry, before and during treatment with ipilimumab, indicated that patients with low frequencies of circulating Lin − CD14 + HLA-DR - M-MDSCs showed an improved clinical response to this therapy [ 103 ]. These data confirm similar findings in other studies in metastatic melanoma patients treated with ipilimumab [ 104 , 105 , 106 ]. Current research is focused on identifying a reliable and clinically relevant method to use MDSC frequency as a biomarker for the clinical response to ipilimumab in melanoma patients [ 107 ].…”
Section: Role Of Mdscs In Resistance To Immunotherapeuticssupporting
confidence: 93%
“…CAP has been widely hailed as a promising anticancer treatment strategy due to its selective targeting of cancer cells [25]. However, relatively little is known about how CAP affects the other cells that make up the melanoma microenvironment, which can greatly influence the therapy outcome [26,27].…”
Section: Cd4 + and Cd8 + T Cells Exhibit A Higher Sensitivity To Cap ...mentioning
confidence: 99%
“…This study also examined the effect of CAP on human monocyte-derived macrophages, another important immune cell type found in the melanoma microenvironment [27]. Resting M0 macrophages were treated with varying amounts of CAP to determine if CAP treatment could affect their viability.…”
Section: Macrophages Are Highly Resistant To Cap and Can Be Polarized...mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the treatment success with checkpoint inhibitors, especially in melanoma, has been ground-breaking both for progression-free and overall survival, only part of the patients show a good response, whereas others do not benefit from this treatment. Many efforts are made to investigate biomarkers to identify and characterize parameters in peripheral blood or tumor microenvironment from melanoma patients to solve this question [19]. In the present study, we investigated immunophenotyping of melanoma, and report on its comparison to flow cytometry and IHC in a relevant preclinical humanized mouse model of melanoma.…”
Section: Introductionmentioning
confidence: 99%